High-efficiency chirality-modulated spoof surface plasmon meta-coupler - Jingwen Duan (Nature Portfolio, 2017)
Abstract Efficiently exciting surface plasmon polaritons (SPP) is highly desired in many photonic applications, but most approaches (such as prism and grating couplers) cannot control flexibly their SPP excitation directions. While Pancharatnam-Berry (PB) metasurfaces were recently proposed to achieve direction-controllable SPP excitations, such scheme suffers from low-efficiency issue due to both direct reflections at the coupler surface and the mode mismatch between the coupler and the guiding-out plasmonic structure. In this article, we solve these issues via imposing two criterions to guide design both the metasurface and the plasmonic metal, based on which a direction-controllable SPP excitation with very high efficiency can be realized. As a proof of concept, we designed/fabricated a realistic device working in the microwave regime, and performed both near-field and far-field measurements to demonstrate that it can achieve an spoof SPP conversion efficiency ~78%, much higher than previous devices. Full-wave simulations are in good agreement with experiments, showing that the efficiency can be further pushed to 92% with optimized designs. Our findings can stimulate spoof SPP-related applications, particularly can help enhance the spin-dependent light-matter interactions in low frequency regime.